The wimpy kid movie diary : how Greg Heffley went Hollywood - Kinney, Jeff. (New York : Amulet Books, 2010)
Go behind the scenes with Jeff Kinney and the making of the Diary of a Wimpy Kid movie! If you've ever wondered how a movie gets made, you're not alone. Author and illustrator Jeff Kinney didn't know either, but when his bestselling series, Diary of a Wimpy Kid, was turned into a live-action movie by 20th Century Fox, he learned how a book gets adapted into a major motion picture. Complete with photographs, script pages, storyboard sketches, costume designs, and original art by Jeff Kinney, The Wimpy Kid Movie Diary is the perfect companion to the bestselling series.
JNF ( ordered JF) ak
Keywords: Diary of a wimpy kid (Motion picture) -- Juvenile literature; Motion pictures -- Production and direction -- Juvenile literature